The impact of social media presence on primary care sports medicine fellowship recruitment: a cross-sectional study - Tiana S. Woolridge; Cooper Bloyd; Madelynn Taylor; Nicolas Hatamiya; Celina de Borja (BMC Medical Education)
Abstract Background The COVID-19 pandemic limited in-person recruitment opportunities for many training programs at academic medical centers. This study aimed to determine the prevalence of social media use among Primary Care Sports Medicine (PCSM) fellowship programs and to investigate the impact of social media on recruitment. Additionally, potential barriers to social media interaction between programs and applicants were examined. Methods A cross-sectional study was conducted using publicly available online sources to identify PCSM fellowship programs and corresponding social media accounts. PCSM Fellowship directors were surveyed regarding their program's use of social media. Prospective PCSM Fellowship Applicants and current fellows were surveyed to determine their interaction with PCSM fellowship social media accounts and how social media influenced their perception of the programs. Results A total of 211 PCSM fellowship programs were identified on the American Medical Society for Sports Medicine (AMSSM) website, of which 83% had a social media presence. The most commonly used platforms were Instagram (43%), Facebook (30%) and Twitter (24%). Fifty-eight individuals who were either current fellows, recently graduated fellows, or current fellowship applicants responded to our survey. Among the surveyed fellows and applicants, 95% reported using social media, with 35% reported following PCSM accounts. Of those who did not follow (N = 38, 65%), the most common reason was lack of awareness of these accounts. Twenty-two percent of respondents indicated that social media positively influenced their perception of a program and its rank list position, while the remainder reported a neutral effect. Forty-seven percent of the fellowship directors reported their program did not have official guidelines for appropriate social media use. Lack of time, resources, and oversight were identified as the most common barriers to social media use. Conclusions A majority of PCSM fellowship programs, fellows, and applicants are present on social media. Social media presence can positively impact an applicant’s view of a program. However, applicants’ lack of awareness of these accounts may serve as a barrier for interaction. The development of universal guidelines for appropriate social media use may help increase adoption and utilization of social media platforms for PCSM fellowship recruitment, particularly during times when in-person recruitment opportunities are limited.